PENGARUH PROGRAM KESEJAHTERAAN KARYAWAN TERHADAP SEMANGAT KERJA KARYAWAN PT PJB UNIT PEMBANGKITAN GRESIK - Putri Retno Wulandari (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2017)
The purpose of this study is to know the influence of employee prosperity program in worker enthusiasm partially or simultaneously and to know the employee prosperity is economical, facilitative and a service which has most domination influence the worker enthusiasm. The population of this study was permanent employee at PT PJB Unit Pembangkitan Gresik. The sample of this study was 109 participants. This study used multiple linier regressions as the technique analysis. The result of this study explained that employee prosperity program was economical and the service has influence the worker enthusiasm partially. Employee prosperity program was economical and the service influenced the worker enthusiasm partially. Employee prosperity program was facilitative and there was no influence in worker enthusiasm. Employee prosperity program was economical, facilitative and the service influence in worker enthusiasm simultaneously. The program also was economical and mostly has domination influence in worker enthusiasm.